Does operator experience affect the accuracy of guided palatal miniscrew insertion via surgical guide? An in-vitro study - Salomone, Amedeo; Palone, Mario; Cremonini, Francesca; Maino, Giuliano; Paoletto, Emanuele; Cappelletti, Marta; Lombardo, Luca (International orthodontics, 2025)
To compare the in-vitro accuracy of guided palatal miniscrew insertion comparing expert and inexpert clinicians. Twenty-one synthetic bone models, derived from a single master model, were acquired to simulate the clinical act of miniscrew insertion. Digital planning and CAD/CAM surgical guide manufacturing were executed by matching the CBCT of the master model with its corresponding STL file. The insertion of two palatal miniscrews in the anterior paramedian region was planned. The operators (mean age 35 years±5 years; 11 males and 9 females) were divided into two sub-groups (inexperienced and experienced), and the miniscrews inserted using a standardized procedure. Linear and angular discrepancies between planned and inserted miniscrew positions were then evaluated at the level of head and tip point by superimposing the reference model (derived from digital planning) with the 20 working models (derived from scanning after miniscrew insertion). Absolute accuracy and comparison between the sub-groups were assessed using a one-sample Wilcoxon test (P<0.05). Regardless of experience, a statistically significant difference in all investigated measurements was found. However, no statistically significant differences were detected between the two sub-groups, except for the sagittal discrepancy at the head, with the inexperienced group being less accurate (P=0.002). The use of a CAD/CAM surgical guide ensures comparable accuracy between inexperienced and experienced clinicians, excepting some outlier discrepancies among the inexpert subjects. Although there are differences in accuracy between the planned and achieved miniscrew position, these differences do not appear to be clinically significant.